Nature and Types of Abusive Behavior against Women - Nahida Mohammad Aljanabi; Athraa Hussein AL-Bahadli (College of Nursing,University of Mosul, 2014)
Background and Objectives: A wide range of studies show that women who have experienced physical or sexual abuse. Therefore, the present study aims to assess the nature and common types of abusive behaviors (physical& psychological) which are imposed up on the women in Bab- Al-Moudham center and to find the relationship of such behaviors with the woman's demographic characteristics. Material and Method: A descriptive study was conducted in Bab- Al-Moudham center in Baghdad city during the period from 15th July to30th September 2011. A convenient (non probability) sample of(200) women at age(20) years and older was selected. The data was collected through the constructed questionnaire and interview technique was employed for the purpose of the study. Data were analyzed through frequency, percentage, chi- square, use cut of point and scoring level: physical abuse\ high 14, moderate 11-13, low 8-10, psychological abuse\ high 20, moderate 16-19, low11-15. Results: Distribution of demographic characteristics showed that the greater number of these women were( 20-24) years old, college graduate, not work, married and coming out from extended family, abusers consanguinity was the husband. Conclusions: The study concluded that most of the women were exposed to some extent of abusive behaviors and the most common ones were screaming and yelling. Keywords: nature types, abusive, behaviors, women.